Hypochromic vitiligo: delineation of a new entity. (1st March 2015) - Ezzedine, K.; Mahé, A.; van Geel, N.; Cardot‐Leccia, N.; Gauthier, Y.; Descamps, V.; Al Issa, A.; Ly, F.; Chosidow, O.; Taïeb, A.; Passeron, T.
Summary: Background: Hypochromic vitiligo is a rare entity that has been reported only twice under the term 'vitiligo minor', with an absence of clear delineation. Objectives: To delineate hypochromic vitiligo through a case series of patients with typical bilateral hypopigmented lesions affecting the face and trunk. Methods: This is a retrospective multicentric evaluation study conducted in eight departments of dermatology in France, Belgium, Senegal and Saudi Arabia. Results: Twenty‐four cases of hypochromic vitiligo were identified. Fourteen were men and 10 women. The mean age at diagnosis was 35·4 years (range 8–66). Strikingly, all patients were dark skinned, with skin types V and VI. The pattern of distribution was highly similar in most of the patients (18 of 24), with involvement of the face and neck area predominating on seborrhoeic areas associated with multiple isolated hypopigmented macules involving predominantly the scalp. The retrospective nature of this study is its main limitation. Conclusions: Hypochromic vitiligo is not yet part of a conventional classification. The disease seems to be limited to individuals with dark skin types. Hypopigmented seborrhoeic face and neck involvement associated with hypopigmented macules of the trunk and scalp is the hallmark of the disease.